2015 IEEE/ACIS 16th International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distribu 2015
DOI: 10.1109/snpd.2015.7176208
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid evolutionary algorithms for data classification in intrusion detection systems

Abstract: Intrusion detection systems (IDS) are important to protect our systems and networks from attacks and malicious behaviors. In this paper, we propose a new hybrid intrusion detection system by using accelerated genetic algorithm and rough set theory (AGAAR) for data feature reduction, and genetic programming with local search (GPLS) for data classification. The AGAAR method is used to select the most relevant attributes that can represent an intrusion detection dataset. In order to improve the performance of GPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Hedar et al [61] proposed a new hybrid IDS based on accelerated genetic algorithm and rough set theory for data feature reduction as well as genetic programming with local search for data classification. In particular, they identified that data feature reduction contributes to improve classification performance and reduce memory and CPU time.…”
Section: Mapping Selected Studies By Ensemble Methodsmentioning
confidence: 99%
“…Hedar et al [61] proposed a new hybrid IDS based on accelerated genetic algorithm and rough set theory for data feature reduction as well as genetic programming with local search for data classification. In particular, they identified that data feature reduction contributes to improve classification performance and reduce memory and CPU time.…”
Section: Mapping Selected Studies By Ensemble Methodsmentioning
confidence: 99%
“…Hedar vd. [34], bir sisteme izinsiz girişleri sınıflandırmak ve belirlemek için genetik algoritma, kaba set teorisi ve genetik programlamaya dayalı bir yöntem önermişlerdir. 25192 sinyal verisinin yanısıra UCI veri tabanından alınan sınıflandırma veri setlerine göre yapılan çalışmanın sonuçları doğru sınıflandırma oranları bakımından özellikle çok katmanlı sinir ağı ve destek vektör makinelerinden oldukça başarılı olduğunu ortaya koymaktadır.…”
Section: Gi̇ri̇ş (Introduction)unclassified